2010
DOI: 10.1007/s00210-010-0575-9
|View full text |Cite
|
Sign up to set email alerts
|

l-3-n-butylphthalide alleviates hydrogen peroxide-induced apoptosis by PKC pathway in human neuroblastoma SK-N-SH cells

Abstract: Alzheimer's disease (AD) is the most common form of dementia. Oxidative stress is one of the earliest events in the neurological and pathological changes of AD. L-3-n-butyl-phthalide (L-NBP), an anti-cerebral ischemia agent, has been shown a potential in AD treatment. In this study, we investigated the neuroprotective effect of L-NBP on hydrogen peroxide (H₂O₂)-induced apoptosis in human neuroblastoma SK-N-SH cells. H₂O₂ significantly reduced cell viability and increased the number of apoptotic-like cells, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Additionally, the expressions of cyclin-dependent kinase and glycogen synthase kinase 3β, the most important kinase involved in tau phosphorylation, were markedly decreased by L-NBP treatment. The effects of L-NBP on decreasing tau phosphorylation and kinase activations also were further confirmed in neuroblastoma SK-N-SH cells, overexpressing wild-type human AβPP695 (SK-N-SH AβPPwt) (Peng et al 2011b). Peng et al (2011a) have also shown that a common chemical component of celery extracts, L-3-n-butyl-phthalide (BTH) reduces amyloid precursor protein processing via mitogen activated protein kinase (MAPK) and protein kinase C pathways as well as attenuating hydrogen peroxide-induced apoptosis in human neuroblastoma cells (Peng et al 2011b;Lei et al 2014).…”
Section: Amelioration Of Neurological Diseasesmentioning
confidence: 71%
“…Additionally, the expressions of cyclin-dependent kinase and glycogen synthase kinase 3β, the most important kinase involved in tau phosphorylation, were markedly decreased by L-NBP treatment. The effects of L-NBP on decreasing tau phosphorylation and kinase activations also were further confirmed in neuroblastoma SK-N-SH cells, overexpressing wild-type human AβPP695 (SK-N-SH AβPPwt) (Peng et al 2011b). Peng et al (2011a) have also shown that a common chemical component of celery extracts, L-3-n-butyl-phthalide (BTH) reduces amyloid precursor protein processing via mitogen activated protein kinase (MAPK) and protein kinase C pathways as well as attenuating hydrogen peroxide-induced apoptosis in human neuroblastoma cells (Peng et al 2011b;Lei et al 2014).…”
Section: Amelioration Of Neurological Diseasesmentioning
confidence: 71%
“…We determined that the activation of the δ-opioid receptor enhances PKC expression. PKC stimulation inhibits the apoptosis of different types of cells (38)(39)(40). Meanwhile, PKC also participates in the protection against hepatic ischemia reperfusion injury and is involved in the processes of cellular proliferation and apoptosis (19,41).…”
Section: Discussionmentioning
confidence: 99%
“…The probable mechanisms of NBP may involve: (1) anti-apoptotic effects - NBP plays the role of anti-apoptosis through a mitochondrion-related caspase-dependent or nondependent apoptotic pathway [8,9,10,11]; (2) anti-oxidative stress - NBP could inhibit mitochondrial permeability, increase the cellular GSH content, and inhibit the overproduction of nitric oxide to play the role of anti-oxidative stress [1], and (3) improve learning and memory deficits - NBP can reduce abnormal phosphorylation of tau protein by downregulating GSK-3β activity [12] or increase alpha-amyloid precursor protein (αAPP) release by increasing PKCα, PKCε activity and MAPK phosphorylation levels to reduce β-amyloid protein (Aβ) generation [13]. Pretreatment with L -NBP could significantly increase cell viability of H 2 O 2 -damaged cells and reduce H 2 O 2 -induced neuronal apoptosis.…”
Section: The Mechanisms Of the Neuroprotective Effect Of Nbpmentioning
confidence: 99%
“…The PKC inhibitor calphostin C significantly attenuated the protective effects of NBP. This suggested that NBP might protect neurons against H 2 O 2 -induced apoptosis by modulating apoptosis-related genes and activating the PKCα pathway [9]. Another study reported that vascular endothelial growth factor expression was upregulated, while the caspase-3 expression was reduced in the diabetes mellitus-NBP rats.…”
Section: The Mechanisms Of the Neuroprotective Effect Of Nbpmentioning
confidence: 99%